Testis structure, spermatogonial niche and Sertoli cell efficiency in Neotropical fish - de Siqueira-Silva, Diógenes Henrique; da Silva Rodrigues, Maira [UNESP]; Nóbrega, Rafael Henrique [UNESP] (Elsevier, 2019)
Neotropical icthyofauna represents one of the most diverse and extreme ecosystems in the world. Likewise, reproduction showed enormous diversity with different reproductive systems, modes and behavior. On the other hand, information on Neotropical fish species, in particular on male reproductive physiology is restricted to few species. This mini-review aimed to compile the existing information on spermatogenesis of Neotropical teleosts focusing on testis structure, spermatogonial niche and Sertoli cell efficiency. The first topic covers the histological analysis of the testicular structure, showing a conserved testicular pattern in relation to the phylogenetic position: basal species present anastomosing tubular testis (e.g. Astyanax altiparanae, Conorhynchos conirostris, Pimelodus maculatus, Lophiosilurus alexandri, Rhinelepis aspera, among others), while derived teleosts showed lobular testis (e.g. Cichlasoma dimerus, Cichla kelberi, Odontesthes bonariensis, Synbranchus marmoratus and others). Next to testicular structure, existing data showed that type A undifferentiated spermatogonia (A und ) is differentially distributed among the Neotropical species. A und can be restricted at the blind-end of the germinal compartment (O. bonariensis), or spread along the germinal epithelium (A. altiparanae), or even distributed along the germinal epithelium but concentrated at the blind-end (C. kelberi and C. intermedia). Moreover, recent studies in A. altiparanae have demonstrated that within the germinal compartment, A und have a preferential distribution in areas neighboring the interstitial compartment – the spermatogonial niche. The proximity with the interstitium suggests that interstitial cells, such as Leydig cells, are important for A und maintenance in the testis. Finally, this mini-review highlighted Sertoli cell efficiency, showing that a single Sertoli cell can support a higher number of germ cells (80–140 spermatids) in Neotropical species evaluated at the moment (e.g. A. altiparanae, Hoplias malabaricus, Poecilia reticulata, Serrasalmus spilopleura, C. intermedia). Overall, this review provided basic and functional information on spermatogenesis of Neotropical species. More studies in this field are necessary since Neotropical region is considered one of the hotspot regions to discovery new species providing, therefore, new opportunities to investigate spermatogenesis in fish.
Keywords: Sertoli cell; Sertoli cell efficiency; Spermatogenesis; Spermatogonial niche; Testis